MASALAH PELAKSANAAN PERKAWINAN BEDA AGAMA PASCA UNDANG-UNDANG NOMOR 1 TAHUN 1974 TENTANG PERKAWINAN (PERBANDINGAN HUKUM PERKAWINAN ISLAM DAN KRISTEN PROTESTAN) - Koerniatmanto Soetoprawiro; Ratna Riyanti (Research Report - Humanities and Social Science, 2012)
There is no rule on the inter-religion marriage law in Indonesia post Regulation number 1, 1974 on Marriage Law. The Problem is, how can be it handled by the Indonesian Positive Law. This is the main problem of this legal research. It was studied with an empirical-legal approach.The results are:1. There is a dispensation rule in Protestant Christian Law. Otherwise, it is absent in Islamic Law.2. The inter-religion marriage law is legal according to the Regulation 1, 1974, because it accepted by Article 2 section (1) of the Regulation. It caused by a Letter of Sacred Marriage of a Protestant Church.3. The inter-religion marriages were registered by the Civil Register as the instruction of the Court.Key words: Inter-religion Marriage, Civil Register, Islamic Law, Protestant Law